Does the employee or former employee have the right to claim compensation under civil law for sickness caused by working conditions which is not an occupational disease - case study - Anna Kowalczyk; Kinga Kulczycka; Ewa Stychno; Beata Chilimoniuk (Kazimierz Wielki University, 2018)
The basic form of compensation for damages incurred as a result of an accident at work or an occupational disease are benefits provided for in the Act on Social Insurance against Accidents at Work and Occupational Diseases of 30 October 2002. If they prove to be insufficient, a person who has suffered an accident at work or an occupational disease may claim supplementary benefits from the employer on the basis of civil law. However, analyses of the health status of the working population in Poland show that occupational diseases are slowly becoming rare, which does not mean that the health status of the working population is improving. Diseases which have been indirectly affected by the development, course or prognosis of the working environment or the way in which it is performed are increasingly recognised. On the basis of the case described, a legal analysis was made in order to answer this research question: does an employee or former employee have the right to claim compensation under civil law for an illness caused by working conditions which is not an occupational disease? The case described above and the legal-dogmatic analysis allow us to conclude that in the Polish legal system it is possible to pursue supplementary claims against the employer in the event of the occurrence of not only occupational diseases, but also other illnesses related to the work performed.